Description and Evaluation of an Emission‐Driven and Fully Coupled Methane Cycle in UKESM1. (20th July 2022) - Folberth, G. A.; Staniaszek, Z.; Archibald, A. T.; Gedney, N.; Griffiths, P. T.; Jones, C. D.; O'Connor, F. M.; Parker, R. J.; Sellar, A. A.; Wiltshire, A.
Abstract: Methane (CH4 ) is one of the most important trace gases in the atmosphere owing to its role as an exceedingly effective greenhouse gas and atmospheric pollutant. Better understanding of the global methane cycle and its interactions with the Earth system is therefore necessary for robust future projections of anthropogenic climate change and assessments of multi‐gas mitigation strategies. Here we present a newly developed methane emission‐driven Earth system model to simulate the global methane cycle fully interactively. We provide an evaluation of methane sources and sinks and a full‐cycle methane budget and its change over the historic period. We further evaluate the methane atmospheric abundance and lifetime against available observations. The new methane emission‐driven model simulates all the components of the methane cycle within observational uncertainty. We calculate a total present‐day (2000–2009 decadal average) methane source of 591 Tg(CH4 ) yr −1 with 197 Tg(CH4 ) yr −1 coming from wetlands. These sources are nearly balanced by the global methane sinks amounting to 580 Tg (CH4 ) yr −1 ; reaction of methane with the hydroxyl radical in the troposphere alone removes 525 Tg(CH4 ) yr −1 . The imbalance between sources and sinks of 11 Tg(CH4 ) yr −1 represents the atmospheric methane growth rate and is in fairly good agreement with current best estimates of 5.8 Tg(CH4 ) yr −1 with a range of 4.9–6.6 Tg(CH4 ) yr −1 . At present‐day the model shows a maximum systematic negative‐bias of approximately 200 ppb in the methane surface mole fraction. Plain Language Summary: Methane is a very important greenhouse gas. The global methane cycle needs to be understood fully to accurately model the way methane affects climate change. We describe a new version of the UKESM1 Earth system model, UKESM1‐ems, that uses emissions of methane to drive the atmospheric chemistry. In case of emissions from global wetlands, such as bogs, swamps and tundra, the methane emissions are calculated by the model during runtime. Methane emissions react directly to changes in the modeled climate. UKESM1‐ems simulates the global cycle of methane from emissions via oxidation in the atmosphere to uptake at the surface more realistically. We also test the model against measurements from satellites and ground‐based stations to ensure the relevant processes in the model behave accurately. The comparison with observations shows that UKESM1‐ems performs well and represents an improvement in simulating important processes in climate and the Earth system. However, we also found that the methane concentration in the model is too low compared to observations for the period of the twentieth and early 21st century during which human activity, especially the use of fossil fuel, is dominating the methane cycle. Key Points: A methane emission‐driven configuration of the UK community Earth system model UKESM1, UKESM1‐ems, has been developed In UKESM1‐ems global wetlands are interactively coupled to the atmosphere at every timestep via methane emissions The UKESM1‐ems performs well simulating the global methane cycle including feedbacks; the global budget compares well with observations